Behavioral and biochemical effects of alcohol withdrawal in female C3H/HeNRj and C57BL/6JRj mice - Tonetto, Simone; Weikop, Pia; Brudek, Tomasz; Thomsen, Morgane (Frontiers in Behavioral Neuroscience, 2023)
Background: alcohol use disorder (AUD) is a major problem of our society and is often characterized and worsened by relapse. Prolonged alcohol exposure leads to numerous biochemical alterations that, upon cessation of alcohol intake, cause an array of immediate and lasting withdrawal symptoms. Acute withdrawal and neuroinflammation can be harmful in themselves, and lasting withdrawal symptoms contribute to relapse. Here, we conducted an initial feasibility study assessing several behavioral and neurochemical factors in female C3H/HeNRj (C3H) and C57BL/6JRj (B6) mice to determine which strain showed the clearest alcohol withdrawal symptoms during long-term abstinence and neurochemical alterations following re-exposure. Methods: Female C3H and B6 mice (n=12) were intermittently exposed to alcohol-containing or control liquid diets for 3 weeks. Acute and prolonged withdrawal symptoms were assessed over a period of 3 weeks using a battery of behavioral test, comprising alcohol self-administration, anhedonia, hyperalgesia, anxiety-like and depressive-like disturbances. Brain inflammation was measured by multiplex cytokine assay. Monoamine levels in the hippocampus and striatum, as well as exploratory analyses of cations levels in the cerebellum, were assessed by High-Performance Liquid Chromatography (HPLC). Results: Both C3H and B6 alcohol-exposed mice displayed decreased saccharin intake or preference and higher stress levels assessed by ultrasonic vocalizations (USVs) recordings. B6 but not C3H alcohol-exposed mice also displayed a slower decline of alcohol oral self-administration (OSA), hyperalgesia , elevated brain TNF-α and elevated serotonin turnover. Conclusions: Our findings highlight the suitability of the B6 strain to study the behavioral and neurochemical alterations caused by alcohol withdrawal and the potential efficacy of experimental treatments, not only in early detoxification, but also in prolonged abstinence. Long-lasting withdrawal symptoms are indeed often the main cause of relapse in alcohol-dependent patients.